Decision time and steps of reasoning in a competitive market entry game - Florian Lindner (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2013)
Entry decisions in market entry games usually depend on the belief about how many others are entering the market, the belief about the own rank in a real effort task, and subjects' risk preferences. In this paper I am able to replicate these basic results and examine two further dimensions: (i) the level of strategic sophistication, which has a positive impact on entry decisions, and (ii) the impact of time pressure, which has a (partly) negative influence on entry rates. Furthermore, when ranks are determined using a real effort task, differences in entry rates are explainable by higher competitiveness of males. Additionally, I show that individual characteristics are more important for the entry decision in more competitive environments.
Keywords: C72; C91; D81; 330; Market entry game; Time pressure; Level-k reasoning; Risk; Competitiveness; Experiment; Markteintritt; Wettbewerb; Asymmetrische Information; Nichtkooperatives Spiel; Test